Reproductive biology of Gerres longirostris Lacepede, 1801 (Perciformes: Gerreidae) in the western Arabian Gulf - Hosny, Chehab F. H.; Al-jaber, Abdulrahman M. (Indian Journal of Fisheries, 2017)
Reproductive biology of the strongspine silverbiddy, Gerres longirostris Lacepede, 1801, was studied by examining 1910 individuals collected fortnightly between May 2012 and January 2014 from the western Arabian Gulf, off Saudi Arabia. The samples were identified as 470 males, 1370 females and 70 undetermined. Maximum length observed was 30 and 40 cm (total length TL) for males and females, respectively. Overall sex ratio of males to females was found to be 1:3.1. This sex ratio was significantly different from the normally expected 1:1 ratio (p0.05). Females were significantly greater than males in all size classes between 20 and 34 cm with high significant difference (p30.28Â°C might not be optimal for reproduction of G. longirostris.